2007
DOI: 10.1096/fj.06-7772com
|View full text |Cite
|
Sign up to set email alerts
|

Enduring vulnerability to reinstatement of methamphetamine‐seeking behavior in glial cell line‐derived neurotrophic factor mutant mice

Abstract: Genetic factors are considered to play an important role in drug dependence/addiction including the development of drug dependence and relapse. With the use of a model of drug self-administration in mutant mice, several specific genes and proteins have been identified as potentially important in the development of drug dependence. In contrast, little is known about the role of specific genes in enduring vulnerability to relapse, a clinical hallmark of drug addiction. Using a mouse model of reinstatement, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 51 publications
1
61
0
Order By: Relevance
“…20,22) We have investigated a role for GDNF in the development and relapse of METH dependence by using intravenous selfadministration and the reinstatement of drug-seeking behavior in GDNF-(ϩ/Ϫ) mice, respectively. 31) The results indicated that GDNF potentiates METH self-administration, enhances motivation to take METH, increases vulnerability to drug-primed reinstatement, and prolongs the cue-induced reinstatement of extinguished METH-seeking behavior. In contrast, there is no significant difference in novelty responses, METH-induced hyperlocomotion and sensitization, food-reinforced operant behavior and motivation, or reinstatement of food-seeking behavior between GDNF-(ϩ/Ϫ) and wild-type littermates.…”
Section: )mentioning
confidence: 95%
See 2 more Smart Citations
“…20,22) We have investigated a role for GDNF in the development and relapse of METH dependence by using intravenous selfadministration and the reinstatement of drug-seeking behavior in GDNF-(ϩ/Ϫ) mice, respectively. 31) The results indicated that GDNF potentiates METH self-administration, enhances motivation to take METH, increases vulnerability to drug-primed reinstatement, and prolongs the cue-induced reinstatement of extinguished METH-seeking behavior. In contrast, there is no significant difference in novelty responses, METH-induced hyperlocomotion and sensitization, food-reinforced operant behavior and motivation, or reinstatement of food-seeking behavior between GDNF-(ϩ/Ϫ) and wild-type littermates.…”
Section: )mentioning
confidence: 95%
“…Our findings suggest that GDNF is a potent antiaddictive factor involved in the development and relapse of METH dependence. 31) CONCLUSION AND REMARKS As reviewed in this article, various cytokines and proteinases are produced in the brain on treatment with drugs of abuse, and act as either pro-addictive or anti-addictive factors. Pro-addictive factors potentiate the rewarding effects of drugs of abuse, and thereby act to facilitate the development of drug dependence.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…GDNF +/À mice have lower levels of GDNF and exhibit greater MA conditioned place preference . GDNF +/À mice acquire stable MA self-administration behavior more quickly than wild-type mice, exhibit greater motivation to self-administer MA (increased dose-response curve for MA self-administration and higher break point on progressive ratio schedule), and display greater reinstatement of prime-and cue-induced drug seeking following extinction, an effect that remained even 6 months after extinction training (Yan et al, 2007). In humans, polymorphisms in the GDNF gene have been associated with age of onset of MA dependence and addiction severity in Japanese MA users (Yoshimura et al, 2011).…”
Section: Neuroinflammation and Ma Dependencementioning
confidence: 99%
“…METH dependence and craving can be modeled by a self-administration paradigm in mice. A recent study demonstrated that glial-derived neurotrophic factor (GDNF) plays an important role in the craving for METH after long-term abstinence using GDNF-deficient mice (3).…”
mentioning
confidence: 99%